Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1088/1741-2560/12/5/056006
|View full text |Cite
|
Sign up to set email alerts
|

A PK–PD model of ketamine-induced high-frequency oscillations

Abstract: Objective Ketamine is a widely used drug with clinical and research applications, and also known to be used as a recreational drug. Ketamine produces conspicuous changes in the electrocorticographic (ECoG) signals observed both in humans and rodents. In rodents, the intracranial ECoG displays a High-Frequency Oscillation (HFO) which power is modulated non-linearly by ketamine dose. Despite the widespread use of ketamine there is no model description of the relationship between the pharmacokinetic-pharmacodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Flores and co-workers 19 modelled the time course of high frequency (∼140 Hz) electrocorticogram oscillations in rats after i.p. ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Flores and co-workers 19 modelled the time course of high frequency (∼140 Hz) electrocorticogram oscillations in rats after i.p. ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of frontal alpha power following propofol administration is thought to result from an increase in thalamocortical synchrony above the observable levels during wakefulness . The occurrence of this phenomenon diminishes or inactivates the functional coupling between regions that maintain consciousness . The presence of frontal alpha power bands strongly suggests that loss of consciousness was achieved by the action of propofol on cortico‐thalamic dynamics in the slow infusion group .…”
Section: Discussionmentioning
confidence: 99%
“…Data are shown from a representative channel (R1). occurrence of this phenomenon diminishes or inactivates the functional coupling between regions that maintain consciousness[6,17,20]. The presence of frontal alpha power bands strongly suggests that loss of consciousness was achieved by the action of propofol on corticothalamic dynamics in the slow infusion group[17].…”
mentioning
confidence: 99%
“…NMDAR antagonists like ketamine or phencyclidine, induce short-lasting psychotic states and is used to study synaptic mechanisms of psychoses in animal models [Frohlich and Van Horn, 2014]. To date, many groups, including our own, have shown that low-doses of ketamine (or related NMDA receptor antagonists) produce HFO in many cortical and subcortical areas [Hunt et al, 2006, Phillips et al, 2012, Caixeta et al, 2013, Flores et al, 2015, Kealy et al, 2017, Amat-Foraster et al, 2019]. However, there are important gaps in understanding ketamine-dependent HFO in the brain, most notably, what are the network and synaptic mechanisms underlying this activity, and does it occur in higher mammals.…”
Section: Introductionmentioning
confidence: 99%